Timing of poverty in childhood and adolescent health: Evidence from the US and UK. (January 2018) - Green, Michael J.; Stritzel, Haley; Smith, Chelsea; Popham, Frank; Crosnoe, Robert
Abstract: Childhood poverty is associated with poorer adolescent health and health behaviours, but the importance of the timing of poverty remains unclear. There may be critical or sensitive periods in early life or early adolescence, or poverty may have cumulative effects throughout childhood. Understanding when poverty is most important can support efficient timing of interventions to raise family income or buffer against the effects of low income, but answers may vary across social contexts. The US and the UK are a useful comparison with similar liberal approaches to cash transfers, but very different approaches to healthcare provision. Utilising data from large population studies in the US (n = 9408; born 1979–1996) and UK (n = 1204; born 1991–1997), this study employs a structured life course approach to compare competing hypotheses about the importance of the timing or pattern of childhood exposure to poverty in predicting adolescent health limitations, symptoms of psychiatric distress, and smoking at age 16 (age 15/16 in US). Household income histories identified experience of poverty (measured as <60% of the national median equivalised income for a given year) in early life (ages 0–5), mid-childhood (ages 6–10) and early adolescence (ages 11–15). The Bayesian Information Criterion (BIC) compared fit across models with variables representing different life course patterns of exposure to poverty. Adolescent distress was not associated with poverty in either country. In both countries, however, variables representing cumulative or persistent experiences of poverty exhibited optimal fit of all poverty exposure variables in predicting adolescent smoking and health limitations. There was also evidence of an early life sensitive period for smoking in the US. Poverty was more persistent in the US, but associations between poverty and outcomes were consistent across countries. Although poverty can have cumulative effects on health and behaviour, early interventions may offer the best long-term protection. Highlights: Poverty in childhood was associated with adolescent smoking and health limitations. Poverty in childhood was not associated with adolescent mental health. Indicators of cumulative or persistent poverty best predicted adolescent outcomes. Poverty was more persistent in the US than the UK. Poverty showed similar associations with adolescent health in the US and UK.